Indicators of ICT development and regional applicability of them - Botos, Szilvia (Acta Agraria Kaposváriensis, 2010)
University of Debrecen, Centre for Agricultural Sciences and Engineering, Faculty of Applied Economics and Rural Development H-4032 Debrecen, Böszörményi str. 138. Today ICT (Information and Telecommunication Technologies) has an essential role in some sectors of the economy. Its development has sped up so much that if somebody is not able to follow this development there is no chance in the economy. It is effectual on both micro and national economic level. A nation’s elementary interest is to make the opportunity to recourse of the more developed ICT, on micro level the enterprises’ interest is to take advantage of it. Furthermore the knowledge-based society comes to the front more and more, because it is a national economic aim, so without reference to conditions ICT is must at everybody’s disposal. So, it has to be available in a little village, as much as a city. If a country can build a suitable infrastructure for the population, it has a huge benefit on international markets and in competitiveness. But in order for the construction of an infrastructure, the first is to ensure the financial sources. EU offers many opportunities on calls for proposals with this object and the most important thing, that we can make the best of it. ICT infrastructure development has been realised on many settlements in Hungary, but not always on the most suitable places. In my opinion, an indicator system would be worthy to develop, by which it would be possible to specify where the development of ICT infrastructure is reasonable – where the use of development funds will be most efficient. Currently applied indicators are deform, they do not reflect the real regional situation, because these had not been worked out to our environmental conditions, but are suitable for only at macro-level, for uniform international comparison, and do not consider many things. Naturally, these are suitable for making international rankings, although such an indicator system would be useful, which shows the development of our own country, at regional level too.